Interaction implant-bone as a micropolar elastic medium: porosity impact of the hard living media. (15th January 2021) - Pierson, Gaël; Njiwa, Richard Kouitat; Bravetti, Pierre
Replacing missing teeth in the dental arch aims to restore the basic function of mastication. In this context, implantology aims to provide long-term solutions. In order to bypass failure issues such as the lack of osseointegration and bone fractures, most of the research work is concerned with the improvement of geometry, surface topography and mechanical properties of the implants. These studies consider bone like a conventional elastic material. Modelling bone as a micropolar elastic material is a way to consider its microstructure. A numerical analysis of the state of stress induced by external loads in the system elastic implant/micropolar bone is analysed. The contribution of the bone microstructure is highlighted.